2017
DOI: 10.1074/jbc.m116.752535
|View full text |Cite
|
Sign up to set email alerts
|

A Single Amino Acid Mutation Converts (R)-5-Diphosphomevalonate Decarboxylase into a Kinase

Abstract: The biosynthesis of isopentenyl diphosphate, a fundamental precursor for isoprenoids, via the mevalonate pathway is completed by diphosphomevalonate decarboxylase. This enzyme catalyzes the formation of isopentenyl diphosphate through the ATP-dependent phosphorylation of the 3-hydroxyl group of ()-5-diphosphomevalonate followed by decarboxylation coupled with the elimination of the 3-phosphate group. In this reaction, a conserved aspartate residue has been proposed to be involved in the phosphorylation step as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 44 publications
2
26
0
Order By: Relevance
“…4A and B). The chemical shift of the signal was in good agreement with the reported chemical shift of the C-3 signal of MVA-3,5-BP, the product of M3P5K from T. acidophilum (10), and with that of MVA-3-P-5-PP, which was produced by SsoDMD mutants that lacked decarboxylation activity (16). Moreover, the signal seemed to acquire an additional hyperfine coupling that resulted from the two-bond 13 C-31 P coupling, which was obvious in the C-3 signals of MVA-3,5-BP and MVA-3-P-5-PP (10,16).…”
Section: Mutation Analysis Of Tacm3ksupporting
confidence: 84%
See 2 more Smart Citations
“…4A and B). The chemical shift of the signal was in good agreement with the reported chemical shift of the C-3 signal of MVA-3,5-BP, the product of M3P5K from T. acidophilum (10), and with that of MVA-3-P-5-PP, which was produced by SsoDMD mutants that lacked decarboxylation activity (16). Moreover, the signal seemed to acquire an additional hyperfine coupling that resulted from the two-bond 13 C-31 P coupling, which was obvious in the C-3 signals of MVA-3,5-BP and MVA-3-P-5-PP (10,16).…”
Section: Mutation Analysis Of Tacm3ksupporting
confidence: 84%
“…The chemical shift of the signal was in good agreement with the reported chemical shift of the C-3 signal of MVA-3,5-BP, the product of M3P5K from T. acidophilum (10), and with that of MVA-3-P-5-PP, which was produced by SsoDMD mutants that lacked decarboxylation activity (16). Moreover, the signal seemed to acquire an additional hyperfine coupling that resulted from the two-bond 13 C-31 P coupling, which was obvious in the C-3 signals of MVA-3,5-BP and MVA-3-P-5-PP (10,16). Slight but obvious changes between the spectra of the samples reacted with or without the E140S mutant were also found in the vicinity of the signals of the other For the data shown in panels A and C, the sample from the negative-control reaction with water was used; for the data shown in panels B and D, the sample from the reaction with the E140S mutant was used.…”
Section: Mutation Analysis Of Tacm3ksupporting
confidence: 84%
See 1 more Smart Citation
“…The C 5 compound IPP is synthesized by the decarboxylation of MVA5PP accompanied by a detachment of its 3-hydroxyl group. To catalyze the reaction, diphosphomevalonate decarboxylase (DMD) consumes ATP to temporarily phosphorylate MVA5PP and form mevalonate 3-phosphate 5-diphosphate inside its catalytic pocket as shown recently by our mutagenic study (3). Detachment of the 3-phosphate group of the intermediate triggers decarboxylation to yield IPP.…”
mentioning
confidence: 91%
“…The γ-phosphate group of ATP is transferred to MVAPP to make the 3′-phosphate-MVAPP intermediate, which is then subjected to dephosphorylation and decarboxylation to produce IPP. Although it was proposed that the ATP-dependent decarboxylation of MVAPP 26 might be initiated via deprotonation of 3′-OH of MVAPP by a conserved aspartic acid (D282 in MDD from Enterococcus faecalis, and D283 in MDD from Staphylococcus epidermidis), followed by the transfer of the γ-phosphate of ATP to MVAPP 27 , recent mutagenesis studies on MDD from Sulfolobus solfataricus (MDD SS ) have demonstrated that the catalytic Asp residue may function in dephosphorylation and decarboxylation of the 3′-phosphate-MVAPP intermediate, rather than deprotonation of the 3′-OH group of MVAPP 28 . However, the phosphoryl transfer efficiencies of the D281T or D281V mutants of MDD SS are lower than the wild-type MDD SS , implying some involvement of the Asp in this step.…”
mentioning
confidence: 99%